2004
DOI: 10.1063/1.1756683
|View full text |Cite
|
Sign up to set email alerts
|

Blue and near-ultraviolet light-emitting diodes on free-standing GaN substrates

Abstract: Blue and near-ultraviolet (UV) InGaN/GaN multiple-quantum-well light-emitting diodes (LEDs) with peak emission at 465 nm and 405 nm, respectively, were grown on GaN and sapphire substrates. The densities of surface and bulk defects in the homoepitaxially grown LEDs were substantially reduced, leading to a decrease in reverse currents by more than six orders of magnitude. At a typical operating current of 20 mA, the internal quantum efficiency of the UV LED on GaN was twice as high compared to the UV LED on sap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 13 publications
3
54
1
Order By: Relevance
“…Therefore the heteroepitaxial growth of thick GaN layers by hydride vapor phase epitaxy (HVPE) has been developed by several groups [1,2] which can be used as quasi-substrates for device epitaxy. On such layers, excellent electronic and optoelectronic devices, in particular laser diodes [3] and light emitting diodes [4], have been fabricated. The HVPE grown layers, however, still suffer from several problems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the heteroepitaxial growth of thick GaN layers by hydride vapor phase epitaxy (HVPE) has been developed by several groups [1,2] which can be used as quasi-substrates for device epitaxy. On such layers, excellent electronic and optoelectronic devices, in particular laser diodes [3] and light emitting diodes [4], have been fabricated. The HVPE grown layers, however, still suffer from several problems.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Several reasons for this behavior have been discussed recently, such as a high device temperature, 4 restricted hole injection, 5 or carrier overflow problems. 3 The role of defects as being responsible for the drop in IQE has not been seriously discussed, despite the very high threading dislocation density in the present LEDs. A much improved behavior is observed for growth on bulk GaN substrates, where the dislocation density is very much reduced.…”
mentioning
confidence: 99%
“…A much improved behavior is observed for growth on bulk GaN substrates, where the dislocation density is very much reduced. 3,6 In recent simulations based on the conventional Shockley-Read-Hall defect recombination scheme for the nonradiative part, it is found that such recombination is insufficient to explain the decrease observed in the IQE at high bias. 4,5 In this paper, we will concentrate on two problems of relevance for a modeling of this decrease of the IQE in InGaN based LEDs.…”
mentioning
confidence: 99%
“…Liu, et al and Cao, et al reported comparable light output for the LEDs on both substrates at low current densities, while the FS-GaN-based LEDs exhibited improved electrical characteristics including leakage current and materials quality. 25,26 In contrast, Kyono, et al reported improved light output for the LEDs on GaN substrates. 27 These observed inconsistencies may arise from inaccurate comparisons.…”
Section: Green Leds Grown On C-plane Sapphire and Free-standing Gan Smentioning
confidence: 99%